The impact of a proposed counseling program during the physical education and sport seance to raise the level of self-confidence for middle school students - bennedjma nourddine (sports creativity, 2025)
The impact of a proposed psychological counseling program during the seance of physical education and sport to raise the level of self-confidence of middle school students ( Field study on third year middle school students). Partial questions : 1- Are there differences in average scores of middle school students (members of the experimental group) on the self-confidence scale between the pre and post measurement? 2-Are there differences between the mean scores of the middle school students of the experimental group and the control group on the self-confidence scale after the application of the proposed counseling program ? 3– Are there any differences between the scores of the experimental group after the final application of the program since two months (follow-up) on the self-confidence scale degree? Study Aims: The main aim of this study is to study the impact of the proposed psychological counseling program during the physical education and sports seance, in increasing the degree of self-confidence ,by applying it to a sample of middle school students and who suffer from the problem of lack self confidence. .study Methodology : we used an experimental method Measurement and re-measurement in a comparative manner in this study .